The Distinctive Writing Style of Arthur Conan Doyle - Kasimova Rano Raxmatulloevna; O`roqova Mexriniso O`ktamovna (Researchparks Publishing, 2022)
Objective: The article is devoted to the writing styles used by great writer Arthur Conan Doyle in his materpieces. Results: Several novels by the author are comparatively analysed together with conclusions are drawn. Plethora of proses coupled with distinctive styles utilized in them are investigated and contrasted as well. The author is noted for his creative and unique features observed in his masterpieces. Conclusion: It is considered that the writer became renowned to the universe for his unparalleled distinctive method. He had a good knowledge about literary styles moreover, he takes advantage of them. As reading his masterpieces one can summon up that the author is master of employing metaphor, metonomy, analogy together with imagery. Apart from these stylistic devices, he managed to utilize well awesome dialogues, plans narrative accomplishment, ability to arouse horror and scenery amid readers.